Does more competition increase business-level innovation? Evidence from domestically focused firms in emerging economies. Issue 5 (4th July 2017) - Crowley, Frank; Jordan, Declan
ABSTRACT: This paper explores the relationship between the level of competition and innovation output for domestically focused businesses in emerging economies in Central and Eastern Europe and Central Asia. It uses survey data from 5054 businesses from the fifth Business Environment and Enterprise Performance Survey. A multivariate probit estimation of the likelihood of different innovation types finds that higher levels of competition are associated with greater likelihood of innovation, but this rises at a decreasing rate as competitor numbers grow. Also, firms operating in economies where competition policy is more effectively enforced are more likely to innovate. However, there is a point where 'too much' competition leads to less innovation – suggesting a tipping point effect. This suggests that policies to maximise competition, as measured by number of competitors, may not be optimal for promoting innovation in emerging economies. This requires a need for more nuanced competition policy approaches. The paper also finds that businesses relying on local markets are significantly less likely to introduce innovations than businesses trading domestically outside their local area, but increased competition in local markets increases the likelihood of businesses introducing product innovation. This points to a local rivalry effect.